Is salivary cortisol moderating the relationship between salivary testosterone and hand-grip strength in healthy men?. Issue 2 (7th February 2017) - Crewther, Blair T.; Thomas, Andrew G.; Stewart-Williams, Steve; Kilduff, Liam P.; Cook, Christian J.
Abstract: This study examined the moderating effect of cortisol (C) on the relationship between testosterone (T) and hand-grip strength (HGS) in healthy young men. Sixty-five males were monitored for salivary T, C and HGS before and 15 min after a short bout (5 × 6-s trials) of sprint cycling exercise. Sprint exercise promoted ( p  < .05) positive changes in T (6.1 ± 24.9%) and HGS (3.4 ± 7.5%), but a negative C response (−14.4 ± 33.1%). The T and C measures did not independently predict HGS, but a significant T × C interaction was found in relation to these outcomes. Further testing revealed that pre-test T and HGS were negatively associated ( p  < .05), but only in men with high C levels. The exercise changes in T and HGS were also negatively related in men with low C levels ( p  < .05), but no relationship was seen in men with high C levels. In summary, complex relationships between T and HGS emerged when considering C as a moderating variable. The pre-test combination of high C and low T levels favoured absolute HGS, whereas low pre-test C levels and a smaller T change were linked to larger HGS changes. These associations suggest that, in the current format, T is not necessarily anabolic to muscle strength in healthy young men. Such complexities could also explain some of the inconsistent T relationships with physical performance in lesser trained male populations.